MOLECULAR DOCKING STUDY OF NOVEL COVID-19 PROTEASE WITH CURRENT CLINICAL MANAGEMENT AGENTS - WADHWA, PANKAJ (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The first case of a new strain of coronavirus (CoV), usually known as CoV disease (COVID)-19, was recognized in Wuhan city of China, in December 2019. Till today, there are no specific treatments available against COVID. During literature searching, it was observed that drugs such as remdesivir, hydroxychloroquine, and chloroquine as their therapeutic options to stop the progress of COVID-19 infections. In the present study, the molecular docking study was performed to understand the binding pattern of selected drugs. Methods: Molecular docking methods were carried out using molecular virtual Docker software using COVID-19 protease (PDB ID 6LU7), and interactions of these three drugs were visualized. Conclusion: All three drugs have shown binding interactions with an active site. We assume that these inhibitory activities helped us to identify the possible drug mechanism and further designing of new molecules or investigate the potential use of other available drugs.